Barriers and facilitators to physical activity participation in adults living with type 1 diabetes: A scoping review protocol - Brennan, M.; Brown, Janie; Ntoumanis, Nikos; Leslie, Gavin (2020)
Objective: The objective of this scoping review is to identify and map barriers to and facilitators of physical activity in adults living with type 1 diabetes.